2009
DOI: 10.1038/sj.bjc.6605496
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and smoking-related lung cancer risk in the Singapore Chinese Health Study

Abstract: BACKGROUND: Smokers with low body mass index (BMI) may be more susceptible to lung cancer. METHODS: We prospectively examined the association between baseline BMI and lung cancer risk in the Singapore Chinese Health Study, a cohort of 63 257 Chinese enrolled between 1993 and 1998. RESULTS: After adjustment for smoking intensity and duration, BMI was inversely associated with risk of lung cancer among current smokers (P for trend ¼ 0.0004). Current smokers at different dosage of smoking with low BMI had signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 27 publications
5
60
2
2
Order By: Relevance
“…This dose-dependent, inverse association was previously reported in case-control [21] and cohort studies [18,22,23,[26][27][28]32]; similarly, the association between weight loss during adulthood and lung cancer risk has been previously reported, albeit less frequently [21][22][23]. We categorized BMI according to the WHO classification, consistent with the studies of Andreotti et al [18] and Kollarova et al [29], whereas most previous studies [21-28, 31, 32, 34] employed percentiles of the study population.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This dose-dependent, inverse association was previously reported in case-control [21] and cohort studies [18,22,23,[26][27][28]32]; similarly, the association between weight loss during adulthood and lung cancer risk has been previously reported, albeit less frequently [21][22][23]. We categorized BMI according to the WHO classification, consistent with the studies of Andreotti et al [18] and Kollarova et al [29], whereas most previous studies [21-28, 31, 32, 34] employed percentiles of the study population.…”
Section: Discussionsupporting
confidence: 61%
“…To solve this problem, cohort studies have excluded cases diagnosed in the first years following enrollment [18,23,27,28,32,33] or used past usual weight [20,22]. These studies still found an increased risk of lung cancer for underweight individuals [18,20,23,27,28,32,33], with the exception of one study [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][7][8][9][10][11][12][13]30 Moreover, the inverse association did not significantly vary by smoking strata. Null associations were mostly reported among never and former smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Araştırmamızda olgu ve kontrol grubu arasında günde içilen sigara sayısı ve sigara paket/yıl bakımından fark saptanmamıştır. Ancak günde içilen sigara sayısı, sigara içme ve bırakma yılı ile akciğer kanseri riski arasında anlamlı ilişki bulunan çalışmalar vardır 12,41,42,44 .…”
Section: Bulgularunclassified